(untitled) (Journal of the College of Basic Education, 2023)
The amount of microorganisms in samples activated sludge from municipal wastewater treatment unit at “ Ristomya ” south of Baghdad region, during different seasons was determined. The total number of microorganisms was greatest during the summer (7.6 x 10 5 cells/ml), whereas the total number of microorganisms was smallest during winter (1.2 x 10 5 cells/ml). The representatives of genus Pseudomonas predominated in quantitative aspect (4.8 x 10 5 cells/ml) , among the bacteria. Actinomycetes were isolated only during the summer months, to reach its total number (1.0 x 10 3 cells/ml ). Molds were found during all seasons, regardless of their small amount in the total number of microorganisms that gave high number (1.0 x 10 3 cells/ml) in winter, whereas yeasts were not found. The application of achieved experiments can help to store the equilibrium in the ratio of the different groups of microorganisms when is trouble in the activated sludge of wastewater treatment unit at extreme regions.